Globalisation, FDI, regional integration and sustainable development : theory, evidence, and policy - Bende-Nabende, Anthony; Bende-Nabende, Anthony (Aldershot, Hants, England ; Burlington, USA : Ashgate, 2002)
Explores the theoretical and empirical literature inter-linking the aforementioned factors from the anti-globalization activists' viewpoint, and from the pro-globalization proponents' perspective. It proposes policies that individual countries should pursue, based on the recognition that globalization generates both positive and negative effects.
Based on: FDI, regionalism, government policy, and endogenous growth. c1999.
Includes bibliographical references (p. 307-316) and index.
oif 11/07/2016
Loans
Keywords: International economic integration; Globalization; Globalization; Globalization; Investments, Foreign; Investments, Foreign; Regionalism; Sustainable development; Sustainable development; Economic policy; Developing countries